LO012: High-risk investigation findings for symptomatic carotid disease in ED TIA patients. (2nd June 2016) - Motamedi, N.; Abdulaziz, K.; Sharma, M.; Perry, J.J.
Abstract : Introduction: About 20% of TIAs are due to large vessel disease. Carotid stenosis >50% which is causing a TIA or stroke needs to be definitely managed quickly in order to benefit. Alternatively, dual antiplatelet therapy may be considered. The objective of this study was to determine high-risk diagnostic findings associated with symptomatic carotid disease in ED patients with TIA to indicate patients requiring urgent carotid imaging.Methods: We performed a prospective Canadian multicenter cohort study, at 13 academic sites, of ED patients with TIA or non-disabling stroke from 2006-2014. Study research nurses recorded imaging findings on standardized data collection forms from the final reports of all imaging tests ordered in the ED on prospectively enrolled patients by treating emergency physicians. Symptomatic carotid disease was defined as carotid stenosis 50-99% or carotid dissection and was adjudicated by stroke neurology to be the etiology of the index event. Patients were followed by medical review and telephone up to 90 days. Univariate analysis was conducted for investigation results with our primary outcome.Results: The cohort included 305 patients with and 5, 277 without symptomatic carotid disease. Positive predictors of symptomatic carotid disease included platelet count over 400 x 10 9 /L (15.3% vs 7.6%; p=0.0095), blood glucose >15 mmol/L (11.4% vs 4.4%; p<0.0001), CT evidence of acute infarction (9.8% vs 4.1%; p<0.0001), CT evidence of old infarction (35.7% vs 24.1%; p<0.0001), and CT evidence of any infarct (43.3% vs 26.7%; p<0.0001). There were no negative predictors of symptomatic carotid disease.Conclusion: High-risk investigation findings suggestive of symptomatic carotid disease in ED TIA patients include platelet count over 400 x 10 9 /L, blood glucose >15 mmol/L, CT evidence of any infarction. Patients with any of these findings should be considered for rapid carotid imaging.